3D Warhol : Andy Warhol and Sculpture. - Evans, Thomas Morgan (IB Tauris, 2017)
Rain machines; alarmed kosher pickle jars filled with gemstones; replica cornflakes boxes; 'disco décor'; time capsules; art bombs; birthday presents; perfume bottles and floating silver pillows that are clouds; paintings that are also films; museum interventions; collected and curated projects; expanded performance environments; holograms. This is a book about the vast array of sculptural work made by Andy Warhol between 1954 and 1987, a period that begins long before the first Pop paintings and ends in the year of his death. In 3D Warhol, Thomas Morgan Evans demonstrates that Warhol's engagem.